PENGARUH STRATEGI PEMBELAJARAN AKTIF MIND MAPS TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA NEGERI 2 KARANGANYAR - Wahyuningsih, Danik; Harlita, Harlita; Ariyanto, Joko (Pendidikan Biologi, 2011)
ABSTRACT - This research aims to find out the effect of the active learning strategy Mind Maps towards students? learning achievement of the class XI IPA at SMA Negeri 2 Karanganyar. This study is a quasi-experimental studies which use Posstest Only Control Group Design. The independent variable in this research is the application of implementation of active learning strategy on Mind Maps whereas the dependent variable is students? achievement in learning biology at 3 levels?, namely, cognitive, affective and psychomotor. The population of the study is the entire class XI at SMA Negeri 2 Karanganyar in academic year 2010/2011. The samples are taken towards control and treatment group. The sample is taken by using Cluster Random Sampling method. The data are collected by using test (for cognitive achievement) whereas for the affective and psychomotor aspects the data are taken by using observation methods. The obtained data are analyzed by using t-test. The result shows that the implementation of active learning strategy has taken good effect towards students? achievement in affective and psychomotor aspects, but has not on the cognitive achievement students in class XI IPA of Karanganyar SMA Negeri 2. Keywords: , Active Learning Strategies, Mind Maps, Biologi Learning Achievement